Physical-Chemical Properties of Edible Film Made from Soybean Residue and Citric Acid - Wenjun Ma; Sami Rokayya; Liang Xu; Xiaonan Sui; Lianzhou Jiang; Yang Li (Journal of Chemistry)
The effect of citric acid on the properties of soybean enzyme-assisted aqueous extraction processing (EAEP) residue edible film was studied. The washed soybean EAEP residue was produced by the process of EAEP. It was determined that the washed soybean EAEP residue is rich in fibers (76.10 ± 1.03%) and has lower oil and protein contents (7.74 ± 0.11% and 3.50 ± 0.20%, resp.). Edible films intended for food packaging have been produced from the washed EAEP residue combined with glycerol, different concentrations of citric acid (0%, 10%, 15%, 20%, 25%, and 30%), and sodium hypophosphite. The spectra have evidenced that the cross-linking reaction of citric acid and fibers has taken place in the residue. 30-CA films showed the highest tensile strength (17.52 MPa) and the lowest water vapor permeability (7.21 g·cm−1·s−1·Pa−1). Also, it indicated that citric acid can cross-link with the hydroxyls of polysaccharide and improve the compatibilization between the polymeric molecules to improve the intermolecular interaction between polysaccharide molecules, so that the water uptake is reduced. The smooth surface and better translucency of the films suggest that the EAEP residue films treated with citric acid are suitable for application in food packaging.